Relationship Between Daily Living Activity Level With Sleep Quality In The Elderly Elderly Social Services UPT, Binjai Social Services North Sumatera In 2021 - Heppi Muliana Situngkir; Lilis Novitarum; Rotua E. Pakpahan (Jurnal EduHealth, 2022)
Activity Daily Living is an activity carried out in the daily life of the elderly, starting from getting up in the morning until going to bed at night. Activity Daily Living is one way that can be done to improve the quality of sleep in the elderly. Sleep quality is a condition in which an individual's sleep results in fitness, freshness and satisfaction with his sleep when he wakes up. This study aims to determine whether there is a relationship betweenLevel Daily Living Activity with Sleep Quality in the Elderly at UPT Social Services for the Elderly, Binjai Social Service, North Sumatra. The type of research design used is correlation with analytical descriptive research design with purposive sampling method sampling as many as 50 respondents. The instruments used in data collection were the Katz Index and PSQI questionnaire sheets. Data analysis using test Spearman rank. The results of the study obtained a significant level of both variables p-value 0.001 (<0.005). This shows that there is a relationship between daily living activities and sleep quality in the elderly at the UPT Social Services for the Elderly, Binjai Social Service, North Sumatra in 2021. It is hoped that respondents can further improve daily living activities so that the quality of sleep for the elderly is better at the UPT Social Services for the Elderly, Binjai Social Service North Sumatra.